Consulting as a threat to local democracy? Flexible management consultants, pacified citizens, and political tactics of strategic development in German cities. Issue 9 (21st October 2018) - Vogelpohl, Anne
ABSTRACT: These days, it is often claimed that democratic procedures are under threat. The detachment of policy decisions from political debates is partly a result of the increasing influence of non-elected organizations and experts. Following a conceptual discussion of the spatiality of democracy, this paper focuses on management consultants as constraint on collective political participation in urban development; namely on McKinsey and Roland Berger. (De-)democratization is assessed alongside processes of inclusion and exclusion of both topics and people from political decisions. Based on a comparison of strategy-making projects in six German cities, the findings reveal three different types of urban policymaking ranging between expert-led and participatory versions. Despite the differences, each of the projects relied on a notion of passive citizens, who primarily need to be "gotten on board" and who lack the power to make decisions. This paper exposes the political tactics involved in an expert-influenced curtailment of democratic procedures.